Transforming education to change the world: the Modern School of Ferrer Guardia. - Nadal-Masegosa, Antonio (University of Newcastle (Australia), 2025)
A historiographic investigation and new conversations about a relevant teaching-learning experience in the history of an education considered alternative, promoting internationalist transformative ideals and methodologies, is the purpose of this paper. It offers a tour of the history of the Modern School for the benefit of historians of education, presents the value of creating a revolutionary school in a dystopian place, and recounts some of its great themes and concepts, as well as its expansion for a new world. Despite a very poor social situation, and the power of religion, the Modern School emerged compiling ideas of progressive educational ideals, with an eagerness to go beyond borders, thanks to its creator, Francisco Ferrer Guardia, which means that more than a century later, both an institution and a human being are objects of study. The history of the Modern School has not been strongly represented in educational history research as a revolutionary, interdisciplinary, and even intersectional subject, as the history of those who were defeated and repressed often is not. Beyond a set of historical facts, its ideals expanded, as they still exist today for whom utopia is not just a dream, but a reality to be achieved.
Este trabajo tuvo como objetivo realizar una investigación historiográfica y generar nuevos diálogos sobre una experiencia de enseñanza-aprendizaje relevante en la historia de una educación considerada alternativa, que promueve ideales y metodologías transformadoras e internacionalistas. Ofrece un recorrido por la historia de la Escuela Moderna para historiadores/as de la educación, presenta el valor de crear una escuela revolucionaria en un contexto distópico, y relata algunos de sus grandes temas y conceptos, así como su expansión hacia un mundo nuevo. A pesar de una situación social muy precaria y el poder de la inquisitorial religión católica, la Escuela Moderna surgió recopilando cuestiones de ideales educativos anarquistas, con un afán por trascender fronteras, gracias a su creador, Francisco Ferrer Guardia, lo que significa que, más de un siglo después, tanto la institución como el ser humano son objeto de estudio. La historia de la Escuela Moderna no ha sido suficientemente representada en la investigación de la historia de la educación como un tema revolucionario, interdisciplinario e incluso interseccional, como suele ocurrir con la historia de quienes fueron derrotados y reprimidos. Más allá de un conjunto de hechos históricos, sus ideales se expandieron, ya que aún existen hoy para quienes la utopía no es solo un sueño, sino una realidad por alcanzar.
Keywords: Educación - Historia; Ferrer i Guàrdia, Francesc - Crítica e interpretación; Pedagogía social; Política y educación; Educación alternativa; Anarquismo; Ateísmo; Innovación educativa; Ferrer Guardia; Historia de la educación; Escuela Moderna; Pedagogía; Racionalismo; Revolución; Cambio social; Métodos de enseñanza; Teoría de la educación